LITERATUR REVIEW TANTANGAN DAN STRATEGI MANAJEMEN KEPALA SEKOLAH DI SEKOLAH DASAR - Nabila Oktavia Ramadhani; Choirun Nisa; Lintang Ayu Hapsari; Kharisma Faiz Azhari; Renggani Amelia Citra Permadanti (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Basic education has a very strategic role in shaping the foundation of knowledge and character of the nation's children. The principal as the main leader in the school environment, holds great responsibility for determining the direction of policy and the success of educational institutions. This study aims to investigate the challenges of being a school principal in managing school management as well as how strategies in dealing with these challenges. The method in this paper uses the literature review method which is used to find data and scientific information about the case under study. The search for articles on the Google scholar uses the help of the Publish or perish application because using the benefit of an application will make it easier to find articles. The selection and screening stages were carried out by analysing the article title, keywords, abstract, background of the problem, author's question, and results and discussion. The results of this study found that as a manager leader, the principal has an important role in influencing education policy making to innovate in order to maintain and improve the quality of education. Key challenges include the lack of technology skills among teachers, especially older ones, and the high cost of technology tools. Effective strategies include visionary leadership, training and professional development of teachers, and provision of technology facilities and infrastructure.